Prevalence of Enterobacteriaceae from Clinical Isolates in Federal Teaching Hospital Gombe, Nigeria - Saleh, Z. M.; Umar, A. T.; Baba, F. A.; Adamu, M. T.; Yarma, A. A.; Isa, S.; Manga, M. M.; Lawal Garba (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt